Kampung rendang - Lilla Nurhuda; Helmi Hasan; Fitri Eriyanti (Jurnal Aplikasi IPTEK Indonesia, 2018)
The purpose of this research is to reveal the form of community support capacity, explain the constraints faced, and the efforts undertaken by the community in maintaining theicon as a village rendang. This research uses etnometodology method by using interview technique, observation and documentation. The results of this study indicate that the form of carrying capacity undertaken by the entrepreneurs are: maintaining the material and quality, maintaining quality improvement of workers and institutional support (cooperative and marketing). Constraints faced are: low technology, lack of human resources (quality of workers), marketing. The efforts undertaken in the community in maintaining the icon as a village rendang namely: utilization of social media and product innovation.